Great dilemmas of spatial planning - Đorđević Dejan; Dabović Tijana (Zbornik Radova: Geografski institut "Jovan Cvijić", 2007)
The planners often forget fundamental, unsolved dilemmas of their profession due to the everyday request and needs, and because those huge problems have permanent nature and they are consequently rarely considered as a main issue. The dichotomy between planning on the one and (neo) liberalism and market mechanisms on the other hand, together with the similar relations between economic development and spatial development and protection of space are always shaping spatial planning. The aim of this paper is to reconsider all those basic questions within the frame of current economic, social and political circumstances the trends.